2011
DOI: 10.1007/s10086-011-1225-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extractions on dynamic mechanical properties of white mulberry (Morus alba)

Abstract: International audienceVibrational properties of wood are affected by several parameters, of which extractives can be one of the most important ones. Wood for European musical instruments has been often studied, but traditional Middle Eastern ones had been left unnoticed. In this study white mulberry (Morus alba L.), the main material for long-necked lutes in Iran, was extracted by five solvents of various polarities (water included). Free-free bar forced vibrations were used to measure longitudinal (L) loss ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
(53 reference statements)
4
23
0
2
Order By: Relevance
“…It is based on three processes applied by Iranian makers on white mulberry (Morus alba), which is a dominant species for making long-necked lutes in Iran (Se Golpayegani et al 2012) as well as other types of lutes from the Middle East to Japan (Yoshikawa 2007). The authors previously reported on how the extractives of this species affected its dynamic mechanical properties (Se Golpayegani et al 2012) and also its toxicity and allergenic sideeffects (Se Golpayegani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on three processes applied by Iranian makers on white mulberry (Morus alba), which is a dominant species for making long-necked lutes in Iran (Se Golpayegani et al 2012) as well as other types of lutes from the Middle East to Japan (Yoshikawa 2007). The authors previously reported on how the extractives of this species affected its dynamic mechanical properties (Se Golpayegani et al 2012) and also its toxicity and allergenic sideeffects (Se Golpayegani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is based on three processes applied by Iranian makers on white mulberry (Morus alba), which is a dominant species for making long-necked lutes in Iran (Se Golpayegani et al 2012) as well as other types of lutes from the Middle East to Japan (Yoshikawa 2007). The authors previously reported on how the extractives of this species affected its dynamic mechanical properties (Se Golpayegani et al 2012) and also its toxicity and allergenic sideeffects (Se Golpayegani et al 2014). After interviewing some instrument makers, laboratory-scale protocols simulating traditional methods were applied to assess their effect on density (ρ) and on the vibrational properties which are classically expressed by E′/ρ (specific modulus of elasticity, where E′: dynamic flexural modulus of elasticity and ρ: Specific gravity) and damping coefficient (tanδ) Norimoto 1984, Obataya et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…mulberry, maple, and walnut; but after some special hydrothermal treatments (Roohnia et al 2011, Segolpayegani et al 2012. Nowadays it has been revealed that hot water extraction of wood during traditional hydrothermal treatment, may withdraw some compounds which are not considered as stress supporting material in lignocellulose micro-structure.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, although, in lower quantities than cell wall constitutive polymers, is even reported in previous studies. To name an example, extractives of wood from Pernambuco (Caesalpinia echinata or Guilandina echinata) have previously been introduced , Matsunaga et al 2000a-b, Alves et al 2008, Segolpayegani et al 2012. It has been shown that the mechanical and acoustical properties of wood from Pernambuco weaken after extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation